Comparison of Different Small Signal Modeling Methods for Bidirectional DC-DC Converter - Ugur, Enes; Vural, Bulent (IEEE, 2014)
Bidirectional dc-dc converters are widely used in applications requiring bidirectional power flow. Control of these converters in a more suitable way and modeling and analyzing of them in a simpler method is still a research topic. In this paper different small signal modeling methods for bidirectional dc-dc converters are compared. Mathematical averaged small signal modeling and ac sweep tool on PSIM simulation software are used to obtain ac response of the converter. These results are compared in terms of bode plots to evaluate accuracy and convenience of the modeling techniques. Step-by-step calculations and simulations are presented together with detailed comparison of simulation results.
Keywords: Energy & Fuels